The use of inter-conversion equations on bituminous binder data - Nur Izzi Md. Yusoff,; Mohd Rosli Hainin,; Mounier, Damien; Airey, Gordon D. (Universiti Kebangsaan Malaysia, 2013)
According to the classical theory of viscoelasticity, a linear viscoelastic (LVE) function can be converted into another viscoelastic function even though they emphasize different information. In this study, dynamic tests were conducted on different conventional penetration grade bitumens using a dynamic shear rheometer (DSR) in the LVE region. The results showed that the dynamic data in the frequency domain can be converted into the time domain functions using a numerical technique. This was done with the aid of the non-linear regularization (NLREG) computer program. The NLREG software is a computer program for solving nonlinear ill-posed problem and is based on non-linear Tikhonov regularization method. The use of data interconversion equation is found suitable for converting from the frequency domain into the time domain of conventional penetration grade bitumens.